Positive impact of virtual reality during wound debridement on quality of life in patients with venous leg ulcers - Spyrka, Kinga; Rojczyk, Ewa; Sieroń, Aleksander; Brela, Jakub; Borkow, Gadi; Kucharzewski, Marek (Frontiers in Virtual Reality, 2025)
IntroductionLocal treatment of venous leg ulcers is often a prolonged and painful process. The latest recommendations from the European Wound Management Association emphasize a holistic approach to patient care, integrating pharmacological and non-pharmacological methods.ObjectiveThe aim of the study was to assess the impact of virtual reality (used during wound cleansing procedure) on the quality of life of patients with venous leg ulcers.MethodsThe randomized controlled trial included 60 patients with venous leg ulcers, who were randomly divided into two groups. The experimental group was exposed to virtual reality during wound cleansing, while the control group did not. Patients’ quality of life was analyzed with the WHOQOL-BREF questionnaire.ResultsAt a follow-up assessment conducted 7 days post-treatment, patients in the experimental group reported significantly higher ratings of overall quality of life—across multiple domains—as well as individual perceptions of health, compared to those in the control group.ConclusionVirtual reality can serve as a supportive therapy in the treatment of venous leg ulcers, acting as a non-pharmacological tool to reduce pain, improve quality of life, and positively influence patients’ attitudes toward treatment.